Early childhood development and its association with women's empowerment in the context of urban poverty in Ethiopia - Tefera Darge Delbiso (Elsevier, 2024)
Background: Empowered women, with increased access to and control over resources, stronger social networks, greater decision-making power, and a more positive gender attitude, significantly contribute to better family well-being. While there is ample evidence regarding the association between child nutrition and women's empowerment, studies examining the association between early childhood development (ECD) and women's empowerment are scarce. Aims: The aim of this study was to estimate the prevalence of ECD delays among 12-36 months old and investigate its association with women's empowerment among the urban poor in Ethiopia. Methods: The study included a sample of 432 women who were unemployed or had irregular employment during the data collection period, along with their children in urban Ethiopia. The ECD was assessed using the Age and Stage Questionnaire (ASQ-3), a tool designed to accurately identify developmental delays in infants and young children and categorized as on track, needs monitoring, and possible delays. Women's empowerment was measured using a multidimensional index that captured access to and control over resources, decision-making power, and social capital, and then categorized into lowest, medium, and highest empowerment levels. The association between ECD domains and women's empowerment was analyzed using ordinal logistic regression, after adjusting for confounders. Results: The study found a high prevalence of delays in ECD domains, with fine motor domain accounting for the largest delay (40.6 %). Children of less empowered mothers are more likely to have the highest development delays in communication (OR=2.22; 95 % CI: 1.36; 3.62), gross motor (OR=1.69; 95 % CI: 1.04; 2.76), problem solving (OR=1.85; 95 % CI: 1.15; 2.98), and personal-social (OR=2.59; 95 % CI: 1.62; 4.15) skills compared to children of more empowered mothers. Conclusions: The study highlights the significance of women's empowerment in promoting ECD, especially in developing countries where ECD programs are fragmented and lacks coordination. Therefore, targeted interventions that improve women's empowerment could lead to improved ECD outcomes.